2015
DOI: 10.1186/s13058-015-0534-y
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitor, suberoylanilide hydroxamic acid (SAHA), enhances anti-tumor effects of the poly (ADP-ribose) polymerase (PARP) inhibitor olaparib in triple-negative breast cancer cells

Abstract: IntroductionOlaparib, a poly (ADP-ribose) polymerase (PARP) inhibitor, has been found to have therapeutic potential for treating cancers associated with impaired DNA repair capabilities, particularly those with deficiencies in the homologous recombination repair (HRR) pathway. Histone deacetylases (HDACs) are important for enabling functional HRR of DNA by regulating the expression of HRR-related genes and promoting the accurate assembly of HRR-directed sub-nuclear foci. Thus, HDAC inhibitors have recently eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(102 citation statements)
references
References 39 publications
7
95
0
Order By: Relevance
“…In the majority of the studies, co-treatment of an HDAC inhibitor with another compound induced the inhibition of tumor growth and showed anti-proliferative effects (46,47,77,84,115,123,138,154). Also, several HDAC inhibitors are assosiated not only with autophagic cell death, but also apoptosis (44,55,70,71,84,97,153).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of the studies, co-treatment of an HDAC inhibitor with another compound induced the inhibition of tumor growth and showed anti-proliferative effects (46,47,77,84,115,123,138,154). Also, several HDAC inhibitors are assosiated not only with autophagic cell death, but also apoptosis (44,55,70,71,84,97,153).…”
Section: Resultsmentioning
confidence: 99%
“…An in vivo study of a MDA-MB-231 xenograft model confirmed this evidence. Moreover, this combination seemed to induce both apoptotic and autophagic cell death, thus enhanced the cytotoxic effects of these inhibitors (46). Further studies could examine more combined treatments of PARP inhibitors with other HDAC inhibitors in order to improve therapeutic approaches for TNBC patients.…”
Section: Hdac Inhibitors As Anti-cancer Agentsmentioning
confidence: 99%
“…The cytotoxic activity of PARP inhibition relies upon unresolved ssDNA damage to create dsDNA breaks upon replication fork collapse and activation of apoptosis (2). Cell-cycle arrest stifles this mechanism and can, in part, provide an explanation for the lack of PARP activity, while loss of PTEN is thought to inhibit response (21). The observed G 1 arrest in response to ROMI in cells with reconstituted BRCA1 (Fig.…”
Section: Brca1 Expression Changes Ddr Expression Profile and Cellularmentioning
confidence: 97%
“…We observed that the MDA-MB-436 cells had reduced HR-mediated repair capacity and were generally less responsive to the combination therapy, which could be attributed to functional loss of BRCA1 (21). We wanted to validate these results using the HCC1937 breast cancer cell line.…”
Section: Checkpoint Activation Is a Key Mechanism In Resistance To Hdmentioning
confidence: 97%
See 1 more Smart Citation